Tailoring the assembly, interfaces, and porosity of nanostructures toward enhanced catalytic activity. Issue 4 (10th October 2014) - Nguyen, Thanh-Dinh; Dinh, Cao-Thang; Do, Trong-On
Abstract : The evolution of nanotechnology has inspired materials scientists to invent nanostructures with achievements in numerous practical applications, particularly in catalysis. Abstract : The evolution of nanotechnology has inspired materials scientists to invent nanostructures with achievements in numerous practical applications, particularly in catalysis. The great advancements typically involve flexible control over the unique properties of the nanomaterial through tuning their structural geometries and components. In this Feature Article, we present the recent progress of our recent research and that of other groups in tailoring the assembly, interfaces, and porosity of diverse inorganic nanostructures. The enhanced catalytic properties of the engineered nanostructures are discussed in relation to photocatalysis, with special emphasis on solar energy conversion, including water splitting, CO2 reduction, and organic photodecomposition. Considering their attributes of superior catalytic performance and long-term durability, the development of economical, active nanocatalysts opens up practical opportunities for endeavours in sustainable energy conversion and other applied fields. This review is expected to introduce readers to the general principles of engineering the nanostructured features of the inorganic nanomaterials capable of improving solar photocatalytic efficiency.